2015
DOI: 10.1017/s0031182015000189
|View full text |Cite
|
Sign up to set email alerts
|

A review of the nest protection hypothesis: does inclusion of fresh green plant material in birds’ nests reduce parasite infestation?

Abstract: The use of aromatic plants and their essential oils for ectoparasite treatment is a field of growing interest. Several species of birds regularly introduce aromatic herbs into their nests putatively to reduce parasites. The behaviour is most often seen in cavity nesting birds and after nest building has finished. The plants are included in a non-structural manner and are often strongly aromatic. Various different hypotheses have been proposed regarding the function of this behaviour; from the plants altering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…In support of this idea, Gwinner & Berger () found fewer bacteria in nests treated with green plants in the European starling. However, most experiments with starlings have not found that green nesting material reduces ectoparasite loads in nests (Fauth et al ., ; Gwinner et al ., ; Brouwer & Komdeur, ; reviewed in Scott‐Baumann & Morgan, ). Furthermore, males did not carry more green plants when nests were experimentally contaminated with ectoparasites (Brouwer & Komdeur, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In support of this idea, Gwinner & Berger () found fewer bacteria in nests treated with green plants in the European starling. However, most experiments with starlings have not found that green nesting material reduces ectoparasite loads in nests (Fauth et al ., ; Gwinner et al ., ; Brouwer & Komdeur, ; reviewed in Scott‐Baumann & Morgan, ). Furthermore, males did not carry more green plants when nests were experimentally contaminated with ectoparasites (Brouwer & Komdeur, ).…”
Section: Discussionmentioning
confidence: 99%
“…PGLS and analysis of transition rates) and also with previous studies (Clark & Mason, ). Because cavities might be more susceptible to be colonized by parasites (Collias & Collias, ; Marshall, ), the use of green plants in cavity‐nesting species suggests that this behaviour likely has a sanitary function in this group (Scott‐Baumann & Morgan, ). In support of this idea, Gwinner & Berger () found fewer bacteria in nests treated with green plants in the European starling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations